1991
DOI: 10.1007/bf00116547
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the subgenus Sophophora of Drosophila derived from large subunit of ribosomal RNA sequences

Abstract: RNA sequencing has been used to assess the relationships among species of the subgenus Sophophora of the genus Drosophila. Two divergent domains, D1 and D2, of the large ribosomal RNA (28S), totalling 550 nucleotides have been sequenced using the rRNA direct sequencing method. A tree has been reconstructed from the neighbor-joining algorithm and the confidence intervals were evaluated by the bootstrap procedure. Results have shown that the branching of the willistoni and saltans groups of the subgenus Sophopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
4
42
2
1
Order By: Relevance
“…The hypothesis supported by morphology, biogeography, and molecular mt 16S (DeSalle, 1991) and nu Adh (Russo et al, 1995) data is shown on the left. The hypothesis supported by analysis of nu 28S rRNA (Pelendakis et al, 1991;Pelendakis and Solignac, 1993) is on the right. …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The hypothesis supported by morphology, biogeography, and molecular mt 16S (DeSalle, 1991) and nu Adh (Russo et al, 1995) data is shown on the left. The hypothesis supported by analysis of nu 28S rRNA (Pelendakis et al, 1991;Pelendakis and Solignac, 1993) is on the right. …”
Section: Discussionmentioning
confidence: 83%
“…Pelendakis et al (1991) and Pelendakis and Solignac (1993), based on neighbor joining analysis of the 28S rRNA locus, suggest that the melanogaster species group, as traditionally defined, is not a monophyletic lineage. The ananassae subgroup, which has traditionally been placed in the melanogaster species group, was shown to be the sister taxon of the obscura species group (Fig.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…They estimate the divergence between the D. montium subgroup and D. melanogaster to be $12.7 MY. Although there are some reports to the contrary (Yang et al 2004), a majority of the other studies estimate that D. ananassae branched off prior to the D. montium subgroup and after the D. obscura group (Pelandakis et al 1991;Pelandakis and Solignac 1993;Clark et al 1998;Harr et al 2000;Goto and Kimura 2001;Tamura et al 2004). We have chosen an approximate estimate of 20 MY for the divergence between D. melanogaster and D. ananassae on the basis of these observations (Table 1).…”
Section: Methodsmentioning
confidence: 99%